Alkaloids, Flavonoids, Tannins and Saponins Contents in Moringa Oleifera Leaves - Kusmiyati Kusmiyati; Ety Rahmawati; Ferry William Frangky Waangsir; Pius Selasa (Indonesian Journal of Global Health Research, 2022)
Various studies have shown that Moringa oleifera leaves have benefits in preventing disease. It also has the potential to solve environmental problems as mosquito larvasides. This is presumably because Moringa leaves contain potentially beneficial compounds. Objective: The aim of this study was to analyze the content of bioactive compounds in Moringa oleifera leaf extract qualitatively and quantitatively. This study was an descriptive study. The study was conducted in Kupang East Nusa Tenggara at September 2019. Moringa leaf extraction was carried out using maceration method with 96% ethanol solvent. The identification of compounds was qualitatively carried out using Thin Layer Chromatography (TLC) methods, while quantitative using spectrophotometric methods. Data was analyzed descriptively to describe the content of flavonoid, tannin, alkaloid, saponin. Study results showed that Moringa leaf extract had flavonoid, alkaloid, tannin and saponin components which were measured qualitatively. Quantitative measurement results showed that Moringa leaves have compounds Total alkaloid Equivalent Quinine 0,3% b/b, Total Flavonoid Equivalent Quercetin17,40 % b/b, Tannin Total Equivalent Tannic Acid 14,68 % b/b, Saponin 7,41% b/b. It is concluded that Moringa oleifera leaf extract has compounds that are beneficial for many things, both in disease prevention, larvasides and other benefits.